Road construction projects from Kg Banir to Route 1, Batang Padang District, Perak / Mohamad Nasaruddin Mohd Nasir - Mohd Nasir, Mohamad Nasaruddin (2015)
Generally, this practical training report clarifies the information about all of theworks, processes and methods on the Construction of Road in F.N Communication Sdn.Bhd. This practical training report is prepared based on day to day and comprehensive program of construction of road gained throughout about 4 months of practical training on a construction site of a F.N Communication. This practical training report is started with explanation and clarification of company background and background of project. The construction of road in a F.N Communication isn’t as easy as it seems in management and planning. Based on the observation made, this construction involved a very detailed methods of constructionand also specific materials that need to be done by skilled workers and also involves a few parties. Besides that, the quality of the workers and the construction materials would also affect the fluency level of the construction works. Also, in this practical training report, the method statement or the work instruction of the construction road methods will be explained thoroughly. Next, this report also explained about the materials used for the construction and the equipment used by the general workers. Moreover, the common problems faced involving in this construction work is also explained in this report along with its suitable steps of solutions. As the conclusion, this practical training report can explain in details about the Construction of Road in F.N Communication practically to all of the readers.